ANALISIS DISPARITAS PUTUSAN HAKIM DALAM PERKARA TINDAK PIDANA DI BIDANG KEHUTANAN (STUDI KASUS PUTUSAN NOMOR 10/PID.SUS/2018/PN WNS DAN PUTUSAN NOMOR 89/PID.B/LH/2020/PN.BLS) - Fitria Fitria; Davit Rahmadan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
In criminal case decisions, it is known that there is a gap in sentencing which is better known asdisparity. The disparity in sentencing has a deep impact, because it contains a constitutional balancebetween individual freedom and the state's right to convict. This can be seen in the judge's decision inthe forestry crime Number 10/Pid.Sus/2018/PN Wns and Decision Number 89/Pid.B/LH/2020/PN.BlsOne decision with another decision which has the characteristics of a criminal offense are the sameand there are similarities in the articles charged but have different decisions. The purpose of writingthis thesis: First, to answer and solve the problem of disparity in decisions on forest destructioncrimes in Decision Number 10/Pid.Sus/2018/PN Wns and Decision Number 89/Pid.B/LH/2020/PN.Bls.Second , to find factors that cause disparities in criminal decisions on forest destruction in decisionsNumber 10/Pid.Sus/2018/PN Wns and Decisions Number 89/Pid.B/LH/2020/PN.Bls. The authorconducts research using normative juridical methods or literature studies in order to obtain secondarydata through documentary studies, namely by studying and analyzing in a comparative deductive waythe laws and regulations with theories that have a relationship to the problems studied.From the results of this study, there are two main problems: First, what is the analysis of thedisparity in the decision on forest destruction in the decision Number 10/Pid.Sus/2018/PN Wns andDecision Number 89/Pid.B/LH/2020/PN.Bls, Second, What are the factors causing the disparity offorest destruction criminal decisions in decisions Number 10/Pid.Sus/2018/PN Wns and DecisionsNumber 89/Pid.B/LH/2020/PN.Bls.The author's suggestion in this study is the importance of understanding the nature of the lawitself. As in the case that has been studied, one of the reasons for the difference is due to a differencein paradigm in viewing the nature of the law itself so that the desired justice is not achieved. LawNumber 18 of 2013 Concerning the Prevention and Eradication of Forest Destruction should not beinterpreted partially, which has implications for the vulnerability of people living around forest areasto being snared by this Law. The paradigm adopted and the method of interpretation applied willaffect the quality of the judge's decision. For this reason, judges need to consider all aspects inmaking a decision.Keywords : Disparity-Crime-Forestry